1998
DOI: 10.1152/ajpendo.1998.275.1.e140
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative insulin and glucose infusion maintains normal insulin sensitivity after surgery

Abstract: Elective surgery was performed after overnight fasting, a routine that may affect the metabolic response to surgery. We investigated the effects of insulin and glucose infusions before and during surgery on postoperative substrate utilization and insulin sensitivity. Seven patients were given insulin and glucose infusions 3 h before and during surgery (insulin group), and a control group of six patients underwent surgery after fasting overnight. Insulin sensitivity and glucose kinetics (d-[6,6-2H2]glucose) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 46 publications
5
63
1
3
Order By: Relevance
“…It has been linked primarily to the invasiveness of surgery. 24,25 Other factors may also contribute, such as the duration of trauma, 26 bed rest and immobilization, 27 type of anesthesia and analgesia, 28,29 nutrition and preoperative fasting, 30,31 blood loss, 25 physical status, and post-surgery rehabilitation. 32 …”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…It has been linked primarily to the invasiveness of surgery. 24,25 Other factors may also contribute, such as the duration of trauma, 26 bed rest and immobilization, 27 type of anesthesia and analgesia, 28,29 nutrition and preoperative fasting, 30,31 blood loss, 25 physical status, and post-surgery rehabilitation. 32 …”
Section: Insulin Resistancementioning
confidence: 99%
“…[141][142][143][144][145] Animal studies have shown that coping with stress is improved when the animals enter the trauma fed, not fasting. 142 Overnight treatment with glucose prevents postoperative decrease in insulin sensitivity 30,146 and early loss of protein after gastrointestinal surgery [147][148][149] and augments voluntary muscle function. 150 Clinical studies conducted in small patient populations reported better outcomes with preoperative nutrition 112,130,[151][152][153][154] and emphasize that avoidance of fasting makes patients less susceptible to complications and may decrease hospital length of stay.…”
Section: Assessment Of Catabolism Before Surgerymentioning
confidence: 99%
“…Insulin interacts with other hormones, and this action is also disturbed after injury. Thus, both IGF-I (Bang et al 1998) and cortisol activity (Nygren et al 1998a) are influenced by lack of insulin action in surgical stress. Lastly, insulin resistance also appears to enhance the inflammatory response .…”
Section: Postoperative Insulin Resistancementioning
confidence: 99%
“…However, on the first postoperative day, patients who received carbohydrates had a smaller reduction, or relative change, in insulin sensitivity compared to the fasted group (-32 ± 4% vs. -55 ± 3%, p<0.01), indicating that postoperative insulin sensitivity is modifiable through preoperative nutrition. This same group carried on to examine patients undergoing total hip replacement surgery (9). Patients who were assigned to the treatment group received glucose and insulin infusions before and during surgery and were studied immediately after surgery to determine if the stress of surgery was better handled in the fed state compared to the fasted state.…”
Section: Perioperative Glucose Infusionsmentioning
confidence: 99%
“…Upon closer examination of this protocol, studies have shown that fasting can intensify the insulin resistance which develops during and after surgery (7,8). This finding led to investigations which examined patients in the fed state prior to surgery through the use of glucose infusions and found improvements in insulin sensitivity following this treatment (9,10). Given that intravenous glucose infusions are costly, invasive and labour-intensive, an oral carbohydrate drink was developed to provide a more efficient method of delivering the carbohydrate load.…”
Section: Introductionmentioning
confidence: 99%